Association analysis of BoLA-DRB3.2 alleles with milk production traits and somatic cells number in La Pampa Holstein cattle (Veterinary Science, 2023)
For many years the selection objective on dairy farms was focused on high yields, ignoring health traits such as disease resistance. Currently the interest is focused in genetically identifying animals that are resistant to developing infectious diseases, through candidate genes. The main Bovine Histocompatibility Complex (BoLA) is a group of genes linked to the immune response. The aim of the present study was to associate alleles of exon 2 of the BoLA-DRB3.2 gene with milk production and somatic cell count as a parameter to evaluate subclinical mastitis. Blood samples were taken from 157 Holstein dairy cows; their DNA was analyzed using the PCR-RFLP technique. Thirty-two alleles were detected, six of which were the most frequent. These are: BoLA-DRB3.2 *23, *24, *16, *25, *28 and *22, with a frequency ranging from 13,50% to 6,43%. Somatic cell counts were analyzed as disease indicators when the records were above 250,000 cells/ml of milk. Using a generalized linear model, allele *25 was found to be associated with a low somatic cell count and *23 was associated with a high somatic cell count (p = 0,03). An association was detected between the alleles and liters of milk (p = 0,0132). No significant association was found with protein and fat percentages. The BoLA-DRB3.2 alleles are evidenced as relevant markers to detect animals genetically resistant to mastitis and higher milk production.
Keywords: BoLA-DRB3.2 gene; Mastitis resistance; Milk production; Somatic cells